Analysis of Suitability and Carrying Capacity of Mangrove Ecotourism in Sedari Village, Karawang District - Hidayat, Wildan Dhya Ulhaq; Riyantini, Indah; Pamungkas, Wahyuniar (E-Journal of Tourism, 2020)
Mangrove nature tourism Sedari Village is an ecotourism location that has the potential to be developed with natural resources that are still awake and an area of mangrove forests around 49.20 Ha. However, in its management, it still does not pay attention to the principles of ecotourism regarding the suitability and carrying capacity for ecotourism. The purpose of this study is to determine the potential in the mangrove nature tourism Sedari Village and assess the suitability and carrying capacity. The method used in this research is survey method and descriptive - quantitative analysis. The results obtained in the mangrove nature tourism Sedari Village there are 4 types of mangroves, namely R. mucronata, R. stylosa, S. alba and A. marina with a mangrove density of 2.055 ind / ha then found 4 types of biota and 2 species namely mullet fish, milkfish , mangrove crabs, little egrets and monitor lizards. For the tourism suitability index value obtained 73% which is included in both the category and the physical carrying capacity obtained 32,800 people / day, the real carrying capacity is 25,047 people / day and the ecological carrying capacity is 26.65 ha. ecological carrying capacity for bridge tracking tourism activities obtained by 55 people / ha and bird watching tourism activities obtained by 165 people / ha. Keywords: mangrove, ecotourism suitability, ecotourism carrying capacity